Fourth Branchial Anomalies: Diagnosis, Treatment, and Long-Term Outcome - Boonen, Annelien; Hens, Greet; Meulemans, Jeroen; Hermans, Robert; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Surgery, 2021)
Introduction: Fourth branchial anomalies, the rarest among anomalies of the branchial apparatus, often present diagnostic and therapeutic challenges. We evaluated the clinical presentation and radiographic features, the treatment and the long-term outcome of patients in this setting. Patients and methods: Of twelve patients treated in the University Hospitals Leuven from 2004 until 2020, twelve variables were collected: date of birth, gender, age of onset of the symptoms, age at final diagnosis, presentation, laterality, previous procedures, diagnostic tools, treatment (open neck surgery, endoscopic laser excision or combination), complications, recurrence and period of follow-up. Descriptive statistics were calculated and results were compared to the existing literature. Results: The most common clinical manifestations were recurrent neck infections with and without abcedation. Definitive diagnosis using direct laryngoscopy, visualizing the internal sinus opening, was possible in all patients. A CT study revealed the typical features of fourth branchial anomalies in seven patients out of nine, an ultrasound study in five out of nine patients. All patients underwent open neck surgery. If this was insufficient, secondary endoscopic laser resection of the ostium at the apex of the piriform sinus was performed (n=4). In 8 patients a thyroid lobectomy was needed for safe complete resection. Postoperative complications were minimal and at long-term, none of the patients showed further recurrence. Average time of follow-up was 8.6 years. Conclusions: Direct laryngoscopy and CT are the most accurate diagnostic tools. Our recommended treatment schedule consists of complete excision of the sinus tract by open neck surgery as the primary treatment because this ensures the best results. In case of recurrence afterwards, endoscopic laser resection of the pharyngeal ostium solved the problem.